2023
DOI: 10.1371/journal.pone.0285774
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to tuberculosis diagnosis and treatment completion in a low-resource setting: A mixed-methods study in the Kingdom of Lesotho

Afom T. Andom,
Hannah N. Gilbert,
Melino Ndayizigiye
et al.

Abstract: Background Lesotho is one of the 30 countries with the highest tuberculosis incidence rates in the world, estimated at 650 per 100,000 population. Tuberculosis case detection is extremely low, particularly with the rapid spread of COVID-19, dropping from an estimated 51% in 2020 to 33% in 2021. The aim of this study is to understand the barriers to tuberculosis diagnosis and treatment completion. Methods We used a convergent mixed methods study design. We collected data on the number of clients reporting sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Stock outs also extended to laboratory commodities. Stock outs of key diagnostics was reported three studies [ 27 , 29 , 44 ]. In relation to the programmatic impact, one study reported that stock out led to service interruption for a duration of up to 15 days [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stock outs also extended to laboratory commodities. Stock outs of key diagnostics was reported three studies [ 27 , 29 , 44 ]. In relation to the programmatic impact, one study reported that stock out led to service interruption for a duration of up to 15 days [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The negative consequences were largest in the poorer districts where a 10% increase in TB drug stock outs led to a 3.25% decline in the TB cure rate and a 2.78% decline in the TB success rate [ 25 ]. Stock outs were found to be associated with financial hardship as patients incurred out-of-pocket expenditures or for go care altogether [ 31 , 44 ]. Stock outs of medicines for children led to higher rates of loss to follow up amongst children [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, malnourished persons are also at increased risk of supratherapeutic concentrations and associated toxicity from drugs like ethambutol and aminoglycosides [30]. Heartbreakingly, some PWTB discontinue their TB therapy because their appetites reappear during TB therapy and they lack access to food [31]. This is illustrated in the following quotation from a mixed methods study in Lesotho: "The challenges that I have recognized is that they make you feel very hungry more often.…”
Section: Treatment Of Tbmentioning
confidence: 99%
“…Sometimes that is bad because there are no piece jobs [daily work] at all. You find that you eat a lot in a short space of time, that doesn't sit well with the wife even though she won't say it, but you will recognize her displeasure" [31].…”
Section: Treatment Of Tbmentioning
confidence: 99%